SOCIAL TRANSFORMATIONS IN THE SOUTHERN REGIONS OF UZBEKISTAN DURING THE SOVIET PERIOD - Nurali Ollomurodov (Web of Journals Publishing, 2025)
The article analyzes the profound social changes in the life of Uzbekistan's population during the Soviet era (1924–1991). It examines the impact of collectivization, industrialization, and the forced labor system on societal structures, as well as reforms in education, healthcare, and gender relations. The article explores the interaction between Soviet policies and local traditions and social institutions, while also assessing the effects of urbanization and Russification on social life. Based on archival documents, historical sources, and sociological analysis, the study contributes to a deeper understanding of the social transformation of Uzbek society during the Soviet period.
Keywords: Social transformation, collectivization, industrialization, urbanization, Russification, education, healthcare, gender equality, kolkhoz, sovkhoz, social structure, local traditions, Soviet policy.